2015
DOI: 10.1504/ijvs.2015.066272
|View full text |Cite
|
Sign up to set email alerts
|

Toward designing pedestrian-friendly vehicles

Abstract: Due to a rise in global urbanization and motorization, pedestrian injuries continue to be a major public-health problem worldwide. To design pedestrian-friendly vehicles, knowledge of common pedestrian injuries, technologies available for reducing these injuries, and benefit estimations for these technologies are essential. In this report, we present a literature review and provide insights into vehicle designs for improving pedestrian safety. Pedestrian-injury data show that heads and lower extremities are th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 52 publications
1
24
0
Order By: Relevance
“…Serious head injuries can be life threatening and/or cause unpredictable consequences. Nowadays, there are many related materials reported in the research of pedestrian head injuries [19,20,21,22,23,24,25,26,27,28,29,30,43]. In addition, the application of HIC [49], maximum positive pressure, and minimum negative pressure [5] in head injuries assessment has been investigated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Serious head injuries can be life threatening and/or cause unpredictable consequences. Nowadays, there are many related materials reported in the research of pedestrian head injuries [19,20,21,22,23,24,25,26,27,28,29,30,43]. In addition, the application of HIC [49], maximum positive pressure, and minimum negative pressure [5] in head injuries assessment has been investigated.…”
Section: Discussionmentioning
confidence: 99%
“…Although numerous studies regarding vehicle–pedestrian crashes have been performed to prevent pedestrian injuries from collisions in developed countries as well as some developing countries [21,22,23,24,25,26,27,28,29,30], it is of particular importance to address some characteristics concerning the relationship between collision parameters and pedestrian injuries, especially in developing countries, such as China. This study explores the characteristics of pedestrian head injuries in car–pedestrian collisions under different parameters by using a statistical analysis method and FEM, which could provide a theoretical basis for automotive design and prevention and treatment of pedestrian injuries.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, in order to assess all the variables involved in the optimization of the frontal component and to be able to compare its performance at different impact conditions, it was considered the impact index defined in equation (1). The coefficient 10 7 was used in this This parameter was calculated for each material configuration and impact case analysed, and then an improvement ratio with respect to the initial prototype was obtained by means of equation (2) Improvement ratio (i, j) = Impact index (material configuration i, impact case j) Impact index initial prototype (impact case j) ð2Þ Figure 22 shows the improvement ratios obtained for all material configurations apart from nos 3 and 7, which presented material failure with excessive damage.…”
Section: Impact Simulations' Resultsmentioning
confidence: 99%
“…3 shows the likelihood of a pedestrian death in relation to vehicle speed. Swedish researchers Erik Rsen and Ulrich Sander found that their predecessors based their findings on pedestrian serious injury or death which overestimated the risk of becoming a fatality [6,7]. Their research shows that the probability of pedestrian fatality is 100% for vehicle speed of app.…”
Section: Introductionmentioning
confidence: 99%